2017
DOI: 10.3390/s17091946
|View full text |Cite
|
Sign up to set email alerts
|

A Behaviour Monitoring System (BMS) for Ambient Assisted Living

Abstract: Unusual changes in the regular daily mobility routine of an elderly person at home can be an indicator or early symptom of developing health problems. Sensor technology can be utilised to complement the traditional healthcare systems to gain a more detailed view of the daily mobility of a person at home when performing everyday tasks. We hypothesise that data collected from low-cost sensors such as presence and occupancy sensors can be analysed to provide insights on the daily mobility habits of the elderly li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…Therefore, development of usable tracking system should be preceded by identification of the aim of tracking, the object to be tracked, and the place where the system would operate.Trace information can be used for different purposes. The most obvious is activity monitoring [2]. The collected data allows for determination of physical activity periods.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, development of usable tracking system should be preceded by identification of the aim of tracking, the object to be tracked, and the place where the system would operate.Trace information can be used for different purposes. The most obvious is activity monitoring [2]. The collected data allows for determination of physical activity periods.…”
mentioning
confidence: 99%
“…The influence of various diseases on gait disorders is discussed in detail in Reference [4]. If monitoring concerns persons with more advanced cognitive impairment stadia, the systems might be used to detect wandering patterns [5][6][7].Post processing of the collected data allows for comparing the person's behaviour with the assumed behaviour model [2]. The difference between the model and the current data may trigger alerts that are usually sent to monitored person's caregivers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…AAL and IoT healthcare related researches as well seems to be more focused on the assessment of the health conditions of the people under monitoring, their behavior (Eisa and Moreira 2017), the adherence to medical treatments (Roy et al 2017), patients' empowerment toward a more conscious healthy lifestyle (Grace et al 2017), or improving their self-sufficiency (Poncela et al 2019). Moreover, most of the studies reported in literature are targeted to the adult and elderly population (Azimi et al 2017), while very few studies foster the effects of smart environments or smart objects on children.…”
Section: Introductionmentioning
confidence: 99%